Composite hydrogel precursor fluid, preparation method and application thereof, and preparation method of anti-swelling medical hydrogel

By using modified silk fibroin, tannin, N-isopropylacrylamide and polylysine components in the composite hydrogel precursor, an anti-swelling medical hydrogel is formed, which solves the deficiency of hemostasis materials during deep tissue and organ damage and bleeding, and achieves rapid and effective hemostasis and wound repair.

CN119570065AInactive Publication Date: 2025-03-07NANTONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411715343.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing hemostatic materials are difficult to effectively stop bleeding during deep tissue and organ damage and bleeding, and are prone to secondary damage and bacterial infection.

Method used

By providing a composite hydrogel precursor consisting of 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid modified silk fibroin, tannic acid, N-isopropylacrylamide and polylysine, it is crosslinked to form an anti-swelling medical hydrogel by ultraviolet light.

Benefits of technology

The hydrogel can quickly form glue under ultraviolet light, adhere closely to damaged tissue, achieve rapid pressure-free hemostasis, and has antibacterial and antioxidant properties, reducing the risk of secondary injury and bacterial infection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570065A_ABST
    Figure CN119570065A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a composite hydrogel precursor fluid, a preparation method and application thereof, and a preparation method of anti-swelling medical hydrogel, and belongs to the field of biomedical engineering. The preparation method comprises the following steps: S1, providing a silk fibroin solution, wherein the silk fibroin solution is an aqueous solution of 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy) butyric acid modified silk fibroin; s2, the tannic acid solution and the silk fibroin solution are mixed, a mixed solution is obtained, and tannic acid in the tannic acid solution is evenly distributed in the mixed solution; and S3, adding N-isopropylacrylamide and polylysine into the mixed solution, and uniformly mixing to obtain the composite hydrogel precursor liquid. Polylysine, tannic acid and N-isopropylacrylamide groups are combined into a cross-linked network of the silk fibroin hydrogel through a photochemical reaction, so that a composite hydrogel precursor solution can be rapidly gelatinized under ultraviolet irradiation and is tightly adhered to damaged tissues, and rapid compression-free hemostasis of wounds is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedical engineering, and specifically relates to a composite hydrogel precursor liquid and a preparation method and application thereof, and a preparation method of an anti-swelling medical hydrogel. Background Art

[0002] Commercial wound hemostatic dressings, such as gauze, gelatin sponges, and bandages, can stop bleeding on superficial wounds by pressing and sealing the wound surface at the bleeding site. However, it is usually inconvenient to stop bleeding by manual pressure when the liver, spinal cord, or brain is injured and bleeding. In addition, the swelling of the hemostatic agent due to water absorption will also cause secondary damage to the injured site and impair organ function. At the same time, the injured site is usually accompanied by a higher risk of bacterial infection, which is also the main cause of death in patients with traumatic bleeding. Therefore, it is urgent to develop a multifunctional, pressure-free wound hemostatic material that has both anti-swelling and excellent antibacterial activity to improve the prognosis of clinical patients.

[0003] Silk fibroin is a natural protein extracted from silkworm cocoons. It has low immunogenicity and good compatibility and has been widely used in the field of regenerative medicine. In terms of hemostasis, silk fibroin hydrogel can bind to fibrinogen and platelets to promote the body's coagulation response.

[0004] However, the lack of effective antibacterial activity, low tissue adhesion and high swelling properties limit the further application of silk fibroin hydrogel materials in hemostasis and wound repair. Summary of the invention

[0005] The purpose of the present invention is to at least partially solve the above technical problems, and to provide a composite hydrogel precursor liquid and a preparation method and application thereof, and a preparation method of an anti-swelling medical hydrogel.

[0006] In a first aspect of the present invention, the present invention provides a method for preparing a composite hydrogel precursor liquid, the preparation method comprising the following steps:

[0007] S1 provides a silk fibroin solution, wherein the silk fibroin solution is an aqueous solution of 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid-modified silk fibroin;

[0008] S2: mixing the tannic acid solution with the silk fibroin solution to obtain a mixed solution, wherein the tannic acid in the tannic acid solution is evenly distributed in the mixed solution;

[0009] S3: adding N-isopropylacrylamide and polylysine into the mixed solution, mixing them evenly, and obtaining a composite hydrogel precursor solution.

[0010] In some embodiments, step S1 includes the following steps:

[0011] S11: dissolving silk fibroin in a solvent, adding 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid, stirring at room temperature in the dark until completely dissolved, reacting for 12h-36h, removing the solvent by rotary evaporation, adding water to dissolve, dialysis, and freeze-drying to obtain 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid-modified silk fibroin;

[0012] S12: dissolving 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid-modified silk fibroin in water to obtain a silk fibroin solution.

[0013] In some embodiments, in step S11, the solvent is selected from hexafluoroisopropanol, deionized water, or any combination thereof.

[0014] In some embodiments, in step S11, the mass ratio of silk fibroin to 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid is (0.1-1):2.

[0015] In some embodiments, the concentration of the silk fibroin solution is 5-15 w / v %.

[0016] In some embodiments, in step S1, mixing the tannic acid solution and the silk fibroin solution specifically includes: mixing and shaking at room temperature; in step S2, mixing evenly specifically includes: mixing evenly at room temperature.

[0017] In a second aspect of the present invention, the present invention provides a composite hydrogel precursor liquid prepared by the above-mentioned preparation method.

[0018] In the third aspect of the present invention, the present invention provides a use of the above-mentioned composite hydrogel precursor liquid in the preparation of a medical hemostatic material.

[0019] In some embodiments, the composite hydrogel precursor liquid is used in the preparation of a medical hemostatic material by irradiating the composite hydrogel precursor liquid with ultraviolet light for 1-3 minutes to obtain the medical hemostatic material.

[0020] In the fourth aspect of the present invention, the present invention provides a method for preparing an anti-swelling medical hydrogel, wherein the anti-swelling medical hydrogel is a medical hemostatic material used for deep tissue and organ injury bleeding. The above-mentioned composite hydrogel precursor fluid is irradiated with ultraviolet light, so that poly-lysine, tannic acid, and N-isopropylacrylamide groups are combined into the formed cross-linked network of silk fibroin hydrogel through photochemical reaction to obtain the anti-swelling medical hydrogel.

[0021] In some embodiments, the intensity of the ultraviolet light is 30-80 mW / cm 2 , wavelength is 365nm, and irradiation time is 1-3min.

[0022] The method for preparing the anti-swelling and anti-oxidative silk fibroin antibacterial hemostatic hydrogel according to the embodiment of the present invention has at least one of the following advantages:

[0023] Polylysine, tannic acid, and N-isopropylacrylamide groups are combined into the cross-linked network of silk fibroin hydrogel through photochemical reaction, so that the composite hydrogel precursor solution can quickly gel under ultraviolet light and adhere tightly to damaged tissue, achieving rapid pressure-free hemostasis of wounds.

[0024] After combining with tissue, the polylysine component in the hydrogel system can interact with the negative charge on the surface of bacteria to cause structural changes in the bacterial cell membrane, resulting in the destruction of the bacterial cell membrane and achieving antibacterial effects; the phenolic hydroxyl group of tannic acid has a strong reducing property and can effectively remove free radicals in the body, thereby exerting an antioxidant effect and promoting wound repair; at the same time, the unique thermosensitive hydrophobic properties of the hydrogel enable it to resist its own swelling at physiological temperature, reducing the secondary damage caused by the hemostatic material to the bleeding injury site. Therefore, the hydrogel is designed to achieve rapid, pressure-free and efficient hemostasis of visceral tissue wounds, prevent bacterial infection at the wound site, prevent secondary damage caused by swelling of the material, and accelerate wound repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] These and / or other aspects and advantages of the present invention will become apparent and readily understood from the following description of the preferred embodiments in conjunction with the accompanying drawings, in which:

[0026] Figure 1 is a comparison chart of the hemostatic performance test results obtained in Test Example 3;

[0027] Figure 2 is a comparison chart of the antioxidant performance test results obtained in Test Example 4;

[0028] Figure 3 is a comparison chart of the anti-resistant bacteria performance test results obtained in Test Example 5;

[0029] Figure 4 This is a comparison chart of the cell compatibility test results obtained in Test Example 6. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further specifically described below by examples and in conjunction with the accompanying drawings. In the specification, the same or similar reference numerals indicate the same or similar components. The following description of the embodiments of the present invention with reference to the accompanying drawings is intended to explain the overall inventive concept of the present invention and should not be construed as a limitation of the present invention.

[0031] An embodiment of the present invention provides a method for preparing a composite hydrogel precursor liquid, the preparation method comprising the following steps:

[0032] S1 provides a silk fibroin solution, wherein the silk fibroin solution is an aqueous solution of 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid-modified silk fibroin.

[0033] Specifically, the silk fibroin solution is prepared by dissolving 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid-modified silk fibroin in water.

[0034] In some embodiments of the present invention, the concentration of 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid modified silk fibroin is 5-15w / v%, such as 6w / v%, 7w / v%, 8w / v%, 9w / v%, 10w / v%, 11w / v%, 12w / v%, 13w / v%, 14w / v%, preferably 10w / v%.

[0035] Specifically, the preparation method of the above-mentioned 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid modified silk fibroin is as follows: dissolve the silk fibroin in a solvent, add 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid, stir at room temperature in the dark until completely dissolved, react for 12h-36h, remove the solvent by rotary evaporation and add water to dissolve, dialyze, and then freeze-dry to obtain 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid modified silk fibroin.

[0036] In some embodiments, the solvent is selected from hexafluoroisopropanol, deionized water, or any combination thereof. In some embodiments, the solvent is preferably hexafluoroisopropanol.

[0037] In some embodiments, the mass ratio of silk fibroin to 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid is (0.1-1):2.

[0038] In some embodiments, the mass ratio of silk fibroin to 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid is 0.45:2.

[0039] In some embodiments, the ratio of silk fibroin, solvent and 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid is (0.1-1) g: 3 mL: 2 g. The dialysis time is 1-5 days, such as 2 days or 3 days.

[0040] S2: mixing the tannic acid solution with the silk fibroin solution to obtain a mixed solution, wherein the tannic acid in the tannic acid solution is evenly distributed in the mixed solution.

[0041] In some embodiments, the concentration of the tannic acid solution is 5% (w / v). The volume ratio of the silk fibroin solution to the tannic acid solution is 1000:(1-10).

[0042] S3: adding N-isopropylacrylamide and polylysine into the mixed solution, mixing them evenly, and obtaining a composite hydrogel precursor solution.

[0043] In some embodiments, the dosage ratio of N-isopropylacrylamide, polylysine and the mixed solution is (0.01-0.1) g: 0.1 g: 1 mL.

[0044] An embodiment of the present invention provides an application of the composite hydrogel precursor liquid prepared by the above preparation method in preparing a medical hemostatic material.

[0045] Specifically, the composite hydrogel precursor fluid is irradiated with ultraviolet light to obtain a medical hemostatic material.

[0046] In some embodiments, the intensity of the UV light is 30-80 mW / cm 2 , wavelength is 365nm, and irradiation time is 1-3min.

[0047] An embodiment of the present invention provides a method for preparing an anti-swelling medical hydrogel, which is a medical hemostatic material used for deep tissue and organ injury bleeding. The above-mentioned composite hydrogel precursor fluid is irradiated with ultraviolet light, so that poly-lysine, tannic acid, and N-isopropylacrylamide groups are combined into the cross-linked network of the formed silk fibroin hydrogel through a photochemical reaction, thereby obtaining an anti-swelling medical hydrogel.

[0048] The catechol groups in tannic acid can react with silk fibroin and tissues through hydrogen bonds, thereby enhancing the tissue adhesion of silk fibroin and exerting an antioxidant effect, thus promoting wound hemostasis and repair.

[0049] Polylysine can stably bind to the 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid group modified in silk fibroin through a photochemical reaction under 365nm ultraviolet light, thus giving the silk fibroin hydrogel material good antibacterial properties. At the same time, N-isopropylacrylamide molecules contain hydrophilic amide groups and hydrophobic isopropyl groups. As a thermosensitive hydrophobic compound, it can also stably bind to the 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid group modified in silk fibroin through a photochemical reaction under 365nm ultraviolet light, which can significantly reduce the swelling of the hydrogel at physiological temperature and reduce the secondary damage to the bleeding site caused by the hemostatic material.

[0050] In some embodiments, the intensity of the ultraviolet light is 30-80 mW / cm 2 , wavelength is 365nm, and irradiation time is 1-3min.

[0051] Example 1

[0052] 0.45 g of silk fibroin was dissolved in 3 mL of hexafluoroisopropanol, and 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid (2 g) was added, and stirred at room temperature in the dark until completely dissolved. The reaction was carried out for 24 h, and the solvent was removed by rotary evaporation, and then water was added to dissolve. The solution was dialyzed for 3 days and lyophilized to obtain 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid-modified silk fibroin.

[0053] The silk fibroin modified with 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid was dissolved in ultrapure water to obtain a 10% (w / v) silk fibroin solution.

[0054] Example 2

[0055] 5% (w / v) tannic acid solution (1 μL) was added to 1 mL of the silk fibroin solution prepared in Example 1, and the mixture was shaken and mixed at room temperature until the tannic acid was evenly distributed in the silk fibroin solution. Then, 0.01 g of N-isopropylacrylamide and 0.1 g of polylysine were added to the mixed solution and mixed at room temperature to obtain a composite hydrogel precursor solution. The hydrogel precursor solution was exposed to 365 nm ultraviolet light (50 mW / cm 2 ) for 2 minutes to form a hydrogel.

[0056] Example 3

[0057] 5% (w / v) tannic acid solution (1 μL) was added to 1 mL of the silk fibroin solution prepared in Example 1, and the mixture was shaken and mixed at room temperature until the tannic acid was evenly distributed in the silk fibroin solution. Then, 0.1 g of N-isopropylacrylamide and 0.1 g of polylysine were added to the mixed solution and mixed at room temperature to obtain a composite hydrogel precursor solution. The hydrogel precursor solution was exposed to 365 nm ultraviolet light (50 mW / cm 2 ) for 2 minutes to form a hydrogel.

[0058] Example 4

[0059] 5% (w / v) tannic acid solution (10 μL) was added to 1 mL of the silk fibroin solution prepared in Example 1, and the mixture was shaken and mixed on a mixing table at room temperature until the tannic acid was evenly distributed in the silk fibroin solution. Then, 0.01 g of N-isopropylacrylamide and 0.1 g of polylysine were added to the mixed solution and mixed evenly at room temperature to obtain a composite hydrogel precursor solution. The hydrogel precursor solution was exposed to 365 nm ultraviolet light (50 mW / cm 2 ) for 2 minutes to form a hydrogel.

[0060] Example 5

[0061] 5% (w / v) tannic acid solution (10 μL) was added to 1 mL of the silk fibroin solution prepared in Example 1, and the mixture was shaken on a mixer at room temperature until the tannic acid was evenly distributed in the silk fibroin solution. Then, 0.1 g of N-isopropylacrylamide and 0.1 g of polylysine were added to the mixed solution and mixed at room temperature to obtain a composite hydrogel precursor solution. The hydrogel precursor solution was exposed to 365 nm ultraviolet light (50 mW / cm 2 ) for 2 minutes to form a hydrogel.

[0062] Test Example 1: Tissue Adhesion Performance Test

[0063] The adhesion strength of the hydrogel to the tissue was determined by lap shear test: the hydrogel prepared in Example 2-5 was cut into a shape with a length of 3 cm, a width of 3 cm, and a height of 1 cm, and used to connect two pieces of pig skin tissue. A universal electronic stretching machine was used to stretch the two pieces of pig skin tissue at a displacement rate of 1 mm / min to test the tissue adhesion strength. The results are shown in Table 1.

[0064] Table 1 Tissue adhesion strength of hydrogels prepared in Examples 2-5

[0065] sample Example 2 Example 3 Example 4 Example 5 Tissue adhesion strength (kPa) 7.68 19.3 43.90 48.33

[0066] Test Example 2: Swelling Performance Test

[0067] The hydrogels prepared in Examples 2-5 were freeze-dried, and the original weight was weighed and recorded as m0. They were then immersed in 37°C physiological saline. The hydrogels were taken out at different time points, the surface moisture was wiped off and weighed, and the mass was recorded as m1. The swelling ratio = (m1-m0) / m0*100%. The swelling ratio of the hydrogels after immersion for 48 hours was shown in Table 2.

[0068] Table 2 Swelling ratio of freeze-dried products in normal saline

[0069] sample Example 2 Example 3 Example 4 Example 5 Swelling ratio (%) 586.2% 70.7% 508.78% 56.2%

[0070] Test Example 3: Hemostasis Performance Test

[0071] The in vivo hemostatic performance of the product was tested using a mouse liver puncture injury model. ICR mice were anesthetized and the liver was exposed. The liver was punctured with a syringe to achieve a bleeding effect. The hydrogel precursor solution prepared in Example 5 was injected into the wound site and immediately exposed to ultraviolet light (50 mW cm -2 Finally, a pre-weighed filter paper was placed on the wound to absorb the blood exuded from the wound after treatment, and the amount of bleeding was recorded and compared with the amount of bleeding from the wound without any treatment.

[0072] like Figure 1As shown, the blood loss of the untreated mice was 23.88 mg, while the blood loss of the mice treated with the hydrogel prepared in Example 5 was only 5.12 mg, which proves that it has good hemostatic properties.

[0073] Test Example 4: Testing the antioxidant capacity of the product using in vitro cell culture.

[0074] After the hydrogel prepared in Example 5 was co-incubated with BV2 cells stimulated with H2O2 for 2 hours, the hydrogel was used to observe the removal of oxygen free radicals in BV2 cells by fluorescence indicator color development, and compared with the group not treated with hydrogel. The stronger the green fluorescence intensity in the cells, the higher the level of reactive oxygen in the BV2 cells. Figure 2 As shown, after hydrogel treatment, the green fluorescence intensity was significantly reduced, proving that the hydrogel has a good ability to scavenge reactive oxygen species.

[0075] Test Example 5: Antibacterial Performance Test

[0076] The antibacterial performance of the hydrogel against common drug-resistant bacteria was tested using the plate coating method. The hydrogel prepared in Example 5 was co-cultured with Escherichia coli and Staphylococcus aureus for 4 hours, and the bacterial solution was aspirated to coat the plate. After 16 hours, the number of colonies on the plate was observed. Figure 3 As shown, the number of bacteria in the hydrogel group decreased significantly, proving that the hydrogel product has good antibacterial properties.

[0077] Test Example 6: Cytotoxicity Test

[0078] The cytotoxicity of the product was tested by in vitro cell culture. L929 cells were planted on the hydrogel prepared in Example 4 (hereinafter referred to as the product) and cultured for 3 days. Cell viability was detected using the Cell Counting Kit-8 kit and compared with that of the simple polyisopropylacrylamide hydrogel. Figure 4 As shown, after 3 days of culture, the survival rate of L929 cells on the product exceeded 98%, while the survival rate of L929 cells in the simple polyisopropylacrylamide hydrogel group was less than 50%, proving that the hydrogel product has good cell compatibility.

[0079] The catechol groups in tannic acid can react with silk fibroin and tissues through hydrogen bonds, enhance the tissue adhesion of silk fibroin and play an antioxidant role, and promote wound hemostasis and repair. Polylysine can stably bind to the 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid group modified in silk fibroin under 365nm ultraviolet light through photochemical reaction, giving the silk fibroin hydrogel material good antibacterial properties; at the same time, N-isopropylacrylamide molecules have hydrophilic amide groups and hydrophobic isopropyl groups. As a thermosensitive hydrophobic compound, it can also stably bind to the 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid group modified in silk fibroin under 365nm ultraviolet light through photochemical reaction, which can significantly reduce the swelling of the hydrogel at physiological temperature and reduce the secondary damage of the hemostatic material to the bleeding site.

[0080] The product of the present invention can enhance its own mechanical properties after ultraviolet light irradiation, adhere to tissues, and effectively stop bleeding within 2 minutes of ultraviolet light irradiation. At the same time, the antibacterial ability of methacrylylated polylysine and the free radical scavenging and antioxidant ability of tannic acid are utilized to achieve the purpose of healing wounds and preventing bacterial infection at the injured part.

[0081] The method for preparing the anti-swelling and anti-oxidative silk fibroin antibacterial hemostatic hydrogel according to the embodiment of the present invention has at least one of the following advantages:

[0082] Polylysine, tannic acid, and N-isopropylacrylamide groups are combined into the cross-linked network of silk fibroin hydrogel through photochemical reaction, so that the composite hydrogel precursor solution can quickly gel under ultraviolet light and adhere tightly to damaged tissue, achieving rapid pressure-free hemostasis of wounds.

[0083] After combining with tissue, the polylysine component in the hydrogel system can interact with the negative charge on the surface of bacteria to cause structural changes in the bacterial cell membrane, resulting in the destruction of the bacterial cell membrane and achieving antibacterial effects; the phenolic hydroxyl group of tannic acid has a strong reducing property and can effectively remove free radicals in the body, thereby exerting an antioxidant effect and promoting wound repair; at the same time, the unique thermosensitive hydrophobic properties of the hydrogel enable it to resist its own swelling at physiological temperature, reducing the secondary damage caused by the hemostatic material to the bleeding injury site. Therefore, the hydrogel is designed to achieve rapid, pressure-free and efficient hemostasis of visceral tissue wounds, prevent bacterial infection at the wound site, prevent secondary damage caused by swelling of the material, and accelerate wound repair.

[0084] Although some embodiments of the present general inventive concept have been shown and described, it will be appreciated by those skilled in the art that changes may be made to these embodiments without departing from the principles and spirit of the present general inventive concept, the scope of which is defined by the claims and their equivalents.

Claims

1. A method for preparing a composite hydrogel precursor liquid, characterized in that: The preparation method comprises the following steps: S1 provides a silk fibroin solution, wherein the silk fibroin solution is an aqueous solution of 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid-modified silk fibroin; S2: mixing the tannic acid solution with the silk fibroin solution to obtain a mixed solution, wherein the tannic acid in the tannic acid solution is evenly distributed in the mixed solution; S3: adding N-isopropylacrylamide and polylysine into the mixed solution, mixing them evenly, and obtaining a composite hydrogel precursor solution.

2. The preparation method according to claim 1, characterized in that: Step S1 includes the following steps: S11: dissolving silk fibroin in a solvent, adding 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid, stirring at room temperature in the dark until completely dissolved, reacting for 12h-36h, removing the solvent by rotary evaporation, adding water to dissolve, dialysis, and freeze-drying to obtain 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid-modified silk fibroin; S12: dissolving 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid-modified silk fibroin in water to obtain a silk fibroin solution with a concentration of 5-15 w / v%.

3. The preparation method according to claim 2, characterized in that: In step S11, the mass ratio of silk fibroin to 4-(4-hydroxymethyl-2-methoxy-5-nitrophenoxy)butyric acid is (0.1-1):

2.

4. The preparation method according to claim 1, characterized in that: In step S1, the mixing of the tannic acid solution and the silk fibroin solution is specifically: mixing and shaking at room temperature; In step S2, the uniform mixing specifically includes: uniform mixing at room temperature.

5. The preparation method according to claim 1, characterized in that: In step S3, the usage ratio of N-isopropylacrylamide, polylysine and the mixed solution is (0.01-0.1) g:0.1 g:1 mL.

6. A composite hydrogel precursor liquid prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the composite hydrogel precursor fluid according to claim 6 in preparing medical hemostatic materials.

8. The use according to claim 7, characterized in that: The composite hydrogel precursor liquid of claim 6 is irradiated with ultraviolet light for 1-3 minutes to obtain a medical hemostatic material.

9. A method for preparing an anti-swelling medical hydrogel, wherein the anti-swelling medical hydrogel is a medical hemostatic material used for deep tissue and organ injury bleeding, characterized in that: The composite hydrogel precursor liquid of claim 6 is irradiated with ultraviolet light to allow polylysine, tannic acid, and N-isopropylacrylamide groups to be combined into the cross-linked network of the formed silk fibroin hydrogel through a photochemical reaction, thereby obtaining an anti-swelling medical hydrogel.

10. The preparation method according to claim 9, characterized in that: The intensity of the ultraviolet light is 30-80 mW / cm 2 , wavelength is 365nm, and irradiation time is 1-3min.

Citation Information

Patent Citations

  • Photosensitive silk fibroin hydrogel as well as preparation method and application thereof

    CN115895280A

  • Polylysine-based antibacterial medical bone tissue adhesive as well as preparation method and application thereof

    CN116350833A

  • Antibacterial hydrogel material with thermosensitivity as well as preparation method and application of antibacterial hydrogel material

    CN118059297A

  • Mechanically active hydrogel for treating intestinal fistula and preparation method thereof

    CN118903553A

  • Hemostatic material

    US20180243465A1